2020
DOI: 10.1007/s00170-020-05232-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weld travel speed on solidification cracking behavior. Part 2: testing conditions and metrics

Abstract: Solidification cracking is a weld defect common to certain susceptible alloys rendering many of them unweldable. It forms and grows continuously behind a moving weld pool within the twophase mushy zone and involves a complex interaction between thermal, metallurgical and mechanical factors. Research has demonstrated the ability to minimize solidification cracking occurrence by using appropriate welding parameters. Despite decade's long efforts to investigate weld solidification cracking, there remains a lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Here, phase transformations can proceed on the steel and titanium interface, leading to intermetallic phase (IMPh) formation [5]. Due to their high values of hardness and brittleness, such IMPh formation leads to hot cracking, which promotes intensive destruction of bimetal plate welded joints [1,6]. Even overheating above 500 °C, owing to structural transformations, can have a negative impact on the mechanical properties of steel-titanium plate joints; in particular, it can lower the fatigue life [7].…”
Section: Introductionmentioning
confidence: 99%
“…Here, phase transformations can proceed on the steel and titanium interface, leading to intermetallic phase (IMPh) formation [5]. Due to their high values of hardness and brittleness, such IMPh formation leads to hot cracking, which promotes intensive destruction of bimetal plate welded joints [1,6]. Even overheating above 500 °C, owing to structural transformations, can have a negative impact on the mechanical properties of steel-titanium plate joints; in particular, it can lower the fatigue life [7].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Chun et al [12] reported the BTR variation based on the segregation concentration behaviour of low-melting point elements (P and S) using a metallurgical analysis model. Recently, Coniglio et al [13] reported the effect of welding speed on BTR change. From a thermomechanical point of view, the occurrence of solidification cracking can be elucidated by the intersection of the high-temperature ductility curve and thermal strain curve [14].…”
Section: Introductionmentioning
confidence: 99%